Looking for (and not finding) a bulk brane - Wyatt Reeves; Moshe Rozali; Petar Simidzija; James Sully; Christopher Waddell; David Wakeham (Journal of High Energy Physics, 2021)
Abstract When does a holographic CFT with a boundary added to it (a BCFT) also have a ‘good’ holographic dual with a localized gravitating end-of-the-world brane? We argue that the answer to this question is almost never. By studying Lorentzian BCFT correlators, we characterize constraints imposed on a BCFT by the existence of a bulk causal structure. We argue that approximate ‘bulk brane’ singularities place restrictive constraints on the spectrum of a BCFT that are not expected to be true generically. We discuss how similar constraints implied by bulk causality might apply in higher-dimensional holographic descriptions of BCFTs involving a degenerating internal space. We suggest (although do not prove) that even these higher-dimensional holographic duals are not generic.